2009
DOI: 10.1002/jssc.200900350
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction of the volatile oil from Santolina chamaecyparissus

Abstract: Supercritical fluid extraction (SFE) of the volatile oil from Santolina chamaecyparissus L. flower heads was performed under different conditions of pressure, temperature, mean particle size and CO(2) flow rate. This oil was compared with the essential oil isolated by hydrodistillation (HD). The SFE volatile and essential oils were analysed by GC and GC-MS. The range of the main volatile components obtained with HD and SFE were, respectively: 1,8-cineole (25-30% and 7-48%), camphor (7-9% and 8-14%), borneol (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The essential oil from this plant was found to have a synergistic antifungal effect against C. albicans when combined with clotrimazole, in both in vitro and in vivo (murine) assays (Suresh et al, 1997). The essential oil of S. chamaecyparissus contains more than 80 constituents, practically all terpenoids, many common to a broad spectrum of plants (Grosso et al, 2009). Combination of the latex of Euphorbia characias , known to contain a high concentration of terpenes, with ketoconazole also resulted in synergistic antifungal activity against C. albicans in in vitro assays (Giordani et al, 2001).…”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 99%
“…The essential oil from this plant was found to have a synergistic antifungal effect against C. albicans when combined with clotrimazole, in both in vitro and in vivo (murine) assays (Suresh et al, 1997). The essential oil of S. chamaecyparissus contains more than 80 constituents, practically all terpenoids, many common to a broad spectrum of plants (Grosso et al, 2009). Combination of the latex of Euphorbia characias , known to contain a high concentration of terpenes, with ketoconazole also resulted in synergistic antifungal activity against C. albicans in in vitro assays (Giordani et al, 2001).…”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 99%
“…Grosso et al . () investigated the EO obtained from S. chamaecyparissus L. flower heads and reported that the main components were 1,8‐cineole (25–30%), camphor (7–9%), borneol (7–8%) and terpinen‐4‐ol (6–7%). Villar et al .…”
Section: Resultsmentioning
confidence: 99%
“…Haggag et al (2000) mentioned that the volatile oil of S. chamaecyparissus fresh arial parts was found to contain 74 identified components: artemisia ketone (35.49%) was the major one. Grosso et al (2009) investigated the EO obtained from S. chamaecyparissus L. flower heads and reported that the main components were 1,8-cineole (25-30%), camphor (7-9%), borneol (7-8%) and terpinen-4-ol (6-7%). Villar et al (1986) analyzed the EO of S. chamaecyparissus ssp.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Monoterpene hydrocarbons (29.5 %) and oxygenated monoterpenes (36.81 %) are the main classes of the essential oil of S. chamaecyparissus from Italy [39], in which, besides artemisia ketone (28.24 %), the other abundant constituents are β-phellandrene (12.78 %), myrcene (8.02 %), and sabinene (7.65 %). Grosso et al [40] compared the essential oil of S. chamaecyparissus (Spain) obtained by SFE with the essential oil obtained by HD, and found 1,8-cineole to be the most abundant component (7-48 % and 25-30 % for SFE and HD, respectively), followed by camphor (8-14 and 7-9 % for SFE and HD, respectively), borneol (2-11 and 7-8 % for SFE and HD, respectively), terpinen-4-ol (1-4 and 6-7 % for SFE and HD, respectively), and terpinolene (1-7 and 1-4 % for SFE and HD, respectively). In previous studies, some S. chamaecyparissus subspecies from Spain were described to contain 1,8-cineole (2-18 %), artemisia ketone (0.1-28 %), camphor (trace-43%), borneol (1-28 %), copaenol (trace-15%), allo-aromadendrene (19 %), and cubenol (1-17 %) as major constituents [12,30].…”
Section: Phytochemicalsmentioning
confidence: 99%